The Histamine H3 Receptor Antagonist E159 Reverses Memory Deficits Induced by Dizocilpine in Passive Avoidance and Novel Object Recognition Paradigm in Rats - Alachkar, Alaa; Łażewska, Dorota; Kieć-Kononowicz, Katarzyna; Sadek, Bassem (Frontiers in Pharmacology, 2017)
The effects of histamine H3 receptor (H3R) antagonist E159 (2.5, 5, and 10 mg/kg, i.p.) on dizocilpine (DIZ)-induced memory deficits were studied in passive avoidance paradigm (PAP) and in novel object recognition (NOR) in adult male rats applying donepezil (DOZ) and pitolisant (PIT) as reference drugs. Acute systemic administration of E159 (2.5, 5, and 10 mg/kg, i.p.) dose-dependently ameliorated the DIZ(0.1mg)-induced memory deficits, and this E159(2.5mg)-provided memory-improving effects in DIZ-induced amnesia were moderately reversed when rats were pretreated with the cholinergic anatagonist scopolamine (SCO, 1 mg/kg, i.p.), H2R antagonist zolantidine (ZOL, 10 mg/kg, i.p.), but not with H1R antagonist pyrilamine (PYR, 10 mg/kg, i.p.). Moreover, the observed memory-enhancing effects of E159 (2.5 mg/kg, i.p.) were strongly abrogated when rats were administered with a combination of ZOL (10 mg/kg, i.p.) and SCO (1.0 mg/kg, i.p.). Furthermore, the significant memory-enhancing effect of E159 (2.5 mg/kg, i.p.) in DIZ-induced short-term memory (STM) impairment in NOR was comparable to the DOZ-provided memory-enhancing effect, and was abrogated when animals were pretreated with the histamine H3R agonist R-(α)-methylhistamine (RAMH, 10 mg/kg, i.p.). However, E159 (2.5 mg/kg, i.p.) failed to provide procognitive effect on DIZ-induced long-term memory (LTM) in NOR. Contrary, the results observed revealed that E159 (2.5 mg/kg) did not alter anxiety levels and locomotor activity of animals naive to elevated-plus maze (EPM), demonstrating that improved performances with E159 (2.5 mg/kg) in PAP or NOR are unrelated to changes in emotional responding or in spontaneous locomotor activity. These results provide evidence for the potential of H3Rs for the treatment of neurodegenerative disorders, e.g. AD.